2006
DOI: 10.1098/rspb.2006.3637
|View full text |Cite
|
Sign up to set email alerts
|

Compliant leg behaviour explains basic dynamics of walking and running

Abstract: The basic mechanics of human locomotion are associated with vaulting over stiff legs in walking and rebounding on compliant legs in running. However, while rebounding legs well explain the stance dynamics of running, stiff legs cannot reproduce that of walking. With a simple bipedal spring-mass model, we show that not stiff but compliant legs are essential to obtain the basic walking mechanics; incorporating the double support as an essential part of the walking motion, the model reproduces the characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
756
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 808 publications
(786 citation statements)
references
References 37 publications
24
756
1
5
Order By: Relevance
“…1.3 m s K1 ; figures 7 and 10), as mechanical energy recovery reaches its maximum ( figure 13a). This coincides with the observation that elephants' metabolic cost of transport ( J kg K1 m K1 ) is minimal at their normal moving speed (Langman et al 1995), consistent with the inference that they may use a passive inverted pendulum (and perhaps some elastic; Geyer et al 2006) mechanism(s) to conserve energy at their optimal speed, like most other terrestrial animals Blickhan & Full 1993;Farley & Ko 1997;Ahn et al 2004;Rubenson et al 2004;Biewener 2006;Biknevicius & Reilly 2006). Their maximal energy recovery may appear to be lower than that of typical walking quadrupeds (approx.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…1.3 m s K1 ; figures 7 and 10), as mechanical energy recovery reaches its maximum ( figure 13a). This coincides with the observation that elephants' metabolic cost of transport ( J kg K1 m K1 ) is minimal at their normal moving speed (Langman et al 1995), consistent with the inference that they may use a passive inverted pendulum (and perhaps some elastic; Geyer et al 2006) mechanism(s) to conserve energy at their optimal speed, like most other terrestrial animals Blickhan & Full 1993;Farley & Ko 1997;Ahn et al 2004;Rubenson et al 2004;Biewener 2006;Biknevicius & Reilly 2006). Their maximal energy recovery may appear to be lower than that of typical walking quadrupeds (approx.…”
Section: Discussionsupporting
confidence: 70%
“…vaulting or bouncing of particular limbs) rather than whole-body CM dynamics (Biewener 2006;Biknevicius & Reilly 2006). However, we caution that the kinematic (Hutchinson et al 2003(Hutchinson et al , 2006 and kinetic (this study; especially figure 13) changes as elephants increase in speed are fairly continuous, perhaps involving a more gradual and subtle gait transition that blurs the distinction between seemingly discrete gaits (also see Ruina et al 2005;Geyer et al 2006). Although this strays dangerously into semantic issues, the shift from vaulting to bouncing hindlimb mechanics we have inferred from slow to fast speeds in elephants is a major change of locomotor function that was not suspected or as thoroughly demonstrated in previous studies, and hence we view it as a distinct gait.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It can thus produce both higher positive work at one joint and a greater negative work at the other, yet experience a smaller change in actual muscle work. In addition, some joint work may be performed passively through elastic energy storage and return by tendon, as has been implicated most strongly for the ankle (Sawicki et al, 2009) but also in the knee and hip (Doke and Kuo, 2007;Geyer et al, 2006). It is therefore likely that positive joint work is an overestimate of actual muscle work, which could explain the relatively high ΔEff.…”
Section: Discussionmentioning
confidence: 79%
“…Lately, Geyer [14] showed that the compliant rather than the stiff legs are essential to obtain the basic walking mechanics, such as ground reaction force (GRF) pattern, and introduced a spring-mass model for walking as well as running. In this paper, inspired by Geyer's study of the compliant legs, we incorporate the virtual spring-damper model into the conventional cart-table model to obtain a more straightened knee walking which is more energy efficient and more comparable to humans.…”
Section: Introductionmentioning
confidence: 99%